Journal of Experimental Zoology Part A: Comparative Experimental Biology
Accès par la licence nationale : https://revue-sommaire.data.istex.fr/ark:/67375/8Q1-ZHF0W3M9-L de 2003 à 2006
Keywords: Médecine vétérinaire